Route selection based on connectivity-delay-trust in public safety networks - Tang, J; Chen, G; Coon, J (IEEE, 2018)
Recently, the mission-critical push-to-talk (MCPTT) system has emerged as the new broadband technology for public safety networks. In this paper, we propose a route selection method based on the connectivity, delay, and trust in the MCPTT system to offer the best connectivity-delay-trust performance. To begin with, the connection probability between a pair of user equipment (UE) has been analyzed with the interference from other MCPTT groups. Then, the timeliness probability is studied to capture the level of confidence for the delay requirement. Moreover, the trust probability is calculated by a beta reputation system to prevent potential attacks from malicious nodes and ensure secure interactions among the forwarding UE. By combining three probabilistic results, we investigate the optimal path route selection method based on the Dijkstra’s algorithm to find the path, which can meet the requirement of the MCPTT system. The simulation results validate our models and theoretical analysis. The results provide a useful insight into designing the MCPTT system for 5G public safety and disaster relief networks.